Effect of Decomposed Fruit Waste on the Growth and Biomass Production of Red Amaranth (Amaranthus cruentus) - Afrin, Syeda Rubaiya; Billah, Shaikh Motasim (South Asian Journal of Agriculture, 2022)
This study attempts to observe the effect of decomposed fruit waste on the growth and biomass production of red amaranth (Amaranthus cruentus). Decomposed fruit waste used as organic fertilizer to ensure soil health. Besides, the use of organic fertilizer instead of using toxic chemical fertilizer is an alternative eco-friendly approach. In this experiment, compost was prepared by using banana and orange peel wrapped in two different poly bags and kept them for 6 months under the soil. Here five treatments and three replications were used in which 1000 kg ha1 and 2000 kg ha-1 orange peel and banana peel composts were used as treatments. Red amaranth was grown as a test crop. After harvesting plants, different growth parameters such as shoot length, root length, leaf number, fresh weight, oven-dry weight and percent of moisture content were measured. The results exhibited that all growth parameters increased significantly by the application of decomposed fruit wastes. However, the application of 2000 kg ha-1 decomposed orange peel performed better in all respects. South Asian J. Agric., 8(1&2): 1-5